ANALISIS MONSUN DI LAUT JAWA - Yosafat Donni Haryanto; Rezfiko Agdialta; Agus Hartoko (Berkala Perikanan Terubuk, 2020)
Monsoon is one of the important atmospheric circulations of the global climate system, monsoon activity has a major influence on weather formation in the region in its path. Monsoon activity is often associated with the presence of synoptic disorders in the area in its path. Synoptic disorders involving the movement of rain slowed throughout the monsoon region. The monsoon pits on an annual cycle related to climate when dry and wet. During the dry season, winters occur on various continents with a mass of air in the atmosphere which results in cold and dry, while when it is wet, it affects the summer with moist air. The Java Sea is an area of 310,000 Km2 which is located only 220 miles from the island of Borneo and the north coast of Java covers the archipelago. The geographical position of the Java Sea is in the area where the interaction is occurring - the atmosphere in the Java Sea is becoming more dynamic. Research Objectives to analyze the influence of rainfall in the Java Sea spatially and temporally. The data used are wind re-analysis of zone and meridional data (ftp.cdc.noaa.gov/ Data set /) from 1986 to 2017, for rainfall data at Tegal, Semarang and Surabaya Meteorological Stations 1986-2017. Spatial and temporal monsoon wind patterns are more dominant and beneficial to the variability of rainfall in the Java Sea. This condition can be seen in the type of monsoonal rain letter U or V with one peak of rain in December January and February (DJF) with the beginning of the rainy season in December in June July August (JJA) peak of the dry season and dry season beginning in June.